Effect of Tutesin Media Utilization on Learning Outcomes Reviewed from Learning Motivation of Second Grade Students at SDN Sidoklumpuk Sidoarjo - Desiningrum, Noviana; Suryandari, Savitri (Riviera Publishing, 2026)
This study aims to find out (1) the difference in learning outcomes between students who participate in learning using tutoring media and students who follow conventional learning, (2) the effect of interaction between learning strategies and student learning motivation on learning outcomes, (3) differences in learning outcomes between students who participate in learning using tutoring media and students who follow conventional learning in students who have high learning motivation, and (4) differences in learning outcomes between students who participate in learning using tutoring media compared to students who follow conventional learning in students who have low learning motivation. The data obtained were analyzed by two-path variance analysis with the F-test. The results showed that: (1) There was a difference in learning outcomes between students who participated in learning using tutoring media and students who participated in conventional learning (FA = 5.008 with p < 0.05), (2) There was an effect of interaction between learning strategies and learning motivation on learning outcomes (FAB = 36.762 with p<0.05); (3) In students who have high learning motivation, there is a difference in learning outcomes between students who follow learning using tutesin media and students who follow conventional learning (t-count = 5,870 > t-table = 1,960), and (4) In students who have low learning motivation, there is a difference in learning achievement between students who follow learning using tutesin media and students who follow conventional learning (t-count = 2,705 > t-table = 1,960). It can be concluded that the implementation of learning using tutoring media has an effect on learning outcomes in grade II students of SDN Sidoklumpuk Sidoarjo.